An Intervention to Involve Family in Decisions about Life Support - Kryworuchko, Jennifer (Université d'Ottawa / University of Ottawa, 2011)
Purpose. To systematically develop and field test an intervention to engage families and healthcare teams in the decision-making process about life support for critically ill patients in the Intensive Care Unit (ICU). Setting. Adult medical-surgical ICU at a Canadian academic teaching hospital. Methods. The International Patient Decision Aid Standards (IPDAS) criteria and the Interprofessional Shared Decision Making (SDM) model guided the study of families facing decisions about life support for their relative in ICU that involved:1) systematic review; 2) qualitative descriptive study; 3) mixed methods field test of a novel patient decision aid (DA). Systematic review findings. Of 3162 citations, four trials evaluated interventions to improve communication between health professionals and patients/families. One intervention met eight of nine criteria for SDM but did not evaluate its effect on the benefit to communication. Qualitative study findings. Six family members and nine health professionals identified two options (life support or comfort care) and values associated with these options. Values included maintaining quality of life, surviving critical illness, minimizing pain and suffering, not being attached to machines, giving the family enough time to adapt emotionally to the patient’s health situation, and the judicious use of healthcare resources. Families were unlikely to become engaged without healthcare professionals making the decision explicit and minimizing other barriers across the decision-making process. Field test findings. Family members and health professionals for eight patients indicated that the DA was feasible to use, acceptable to users, had the potential to do what was intended, and did not seem to present adverse consequences to users. An enhanced delivery strategy is needed for future evaluation of its effect on facilitating patient/family involvement in decisions. Conclusions. Limited involvement of families in the process of decision-making about life support in the ICU reinforced the need for effective interventions to facilitate SDM. These studies validated the operationalization of the IPDAS criteria, as part of a systematic process for developing and field testing DAs. However, IPDAS criteria stop short of elements necessary to consider when implementing the DA in the processes of care.
Keywords: Shared Decision Making; Patient Involvement; Life Support; Intensive Care Unit; Family; Withholding Life Support; Systematic Review; Mixed method; Qualitative; Manuscript based thesis